Economics of Milk Production and its Constraints: A Case Study of Himachal Pradesh - Thakur, Niyati; Amit; Dr. Shilpa (Indian Journal of Dairy Science, 2023)
An attempt has been made in this investigation to work out the cost and returns from milk production across different milch species of animals. Tabular analysis was employed to work out the cost and returns while Garrett’s Ranking Technique (GRT) was used to identify the major constraints in milk production. The multistage random sampling technique was adopted to select the sample of 60 dairy farmers. Average milk yield per day per animal was found to be significantly higher in case of crossbred cow (7.05 litres) as compared to local cow (2.88 litres). Similarly, net maintenance cost per milch animal per day was found to be relatively higher in crossbred cow (₹ 203.86) as compared to local cow (₹ 115.71). The per litre cost of milk production was observed to be significantly higher in case of local cow (₹ 35.77) followed by crossbred cow (₹ 26.81). The net income per day was relatively higher in case of crossbred cow (₹ 61.52) as compared to local cow (₹ 2.33), while it was found negative in small herd size category for local cow (- ₹ 0.16). The net return from crossbred cow was more than that of local cows indicating crossbred milking cow was more economical than the local cow in the study area. The Cobb-Douglas production function revealed that concentrate and green fodder had positive and significant (p